2005
DOI: 10.1073/pnas.0501594102
|View full text |Cite
|
Sign up to set email alerts
|

Domain III of Plasmodium falciparum apical membrane antigen 1 binds to the erythrocyte membrane protein Kx

Abstract: Plasmodium falciparum apical membrane antigen 1 (AMA1) is located in the merozoite micronemes, an organelle that contains receptors for invasion, suggesting that AMA1 may play a role in this process. However, direct evidence that P. falciparum AMA1 binds to human erythrocytes is lacking. In this study, we determined that domain III of AMA1 binds to the erythrocyte membrane protein, Kx, and that the rate of invasion of Kx null erythrocytes is reduced, indicating a significant but not unique role of AMA1 and Kx … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
67
2
4

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(76 citation statements)
references
References 24 publications
3
67
2
4
Order By: Relevance
“…Antibodies against AMA1 inhibit invasion ( Thomas et al, 1984;Deans et al, 1988;Hehl et al, 2000;Kocken et al, 2000;Mitchell et al, 2004), as do phage-displayed peptides derived from (Urquiza et al, 2000) or with affinity for Plasmodium AMA1 (Li et al, 2002;Keizer et al, 2003). Together with trans-species complementation experiments (Triglia et al, 2000) and heterologous expression experiments (Fraser et al, 2001;Kato et al, 2005), these data suggest that AMA1 plays a role in host cell invasion, perhaps as an adhesin. However, it has not previously been possible to disrupt AMA1 for phenotypic analysis, in any apicomplexan parasite, presumably because AMA1 is an essential gene (Mital and Ward, unpublished results;Hehl et al, 2000;Triglia et al, 2000).…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…Antibodies against AMA1 inhibit invasion ( Thomas et al, 1984;Deans et al, 1988;Hehl et al, 2000;Kocken et al, 2000;Mitchell et al, 2004), as do phage-displayed peptides derived from (Urquiza et al, 2000) or with affinity for Plasmodium AMA1 (Li et al, 2002;Keizer et al, 2003). Together with trans-species complementation experiments (Triglia et al, 2000) and heterologous expression experiments (Fraser et al, 2001;Kato et al, 2005), these data suggest that AMA1 plays a role in host cell invasion, perhaps as an adhesin. However, it has not previously been possible to disrupt AMA1 for phenotypic analysis, in any apicomplexan parasite, presumably because AMA1 is an essential gene (Mital and Ward, unpublished results;Hehl et al, 2000;Triglia et al, 2000).…”
Section: Introductionmentioning
confidence: 75%
“…Many microneme proteins are thought to function as host cell adhesins (Tomley and Soldati, 2001), and AMA1 has been postulated to play such a role (Fraser et al, 2001;Kato et al, 2005;Pizarro et al, 2005). The ability of AMA1/AMA1-myc and ⌬ama1/AMA1-myc parasites to bind to host cells was therefore compared using a laser scanning cytometer-based attachment assay.…”
Section: A Tgama1 Deficiency Does Not Affect the Early Steps Of Invasionmentioning
confidence: 99%
“…Furthermore, they found that the contiguous domain I/II was required for efficient binding. In contrast, Kato and others (19) report that the RBC protein Kx is the receptor for PfAMA1 and that it is domain III of PfAMA1 that mediates this binding. We have obtained similar binding profiles for native BdAMA1 to wildtype and Kx null cells (data not shown), which demonstrates that Kx is not the erythrocyte receptor for BdAMA1.…”
Section: Discussionmentioning
confidence: 98%
“…Attempts to explore its erythrocyte-binding capabilities have provided contradictory results, with the identification of either domains I and II of Plasmodium yoelii AMA1 (10) or domain III of PfAMA1 (19) being critical for this function. We took advantage of the high yields of native BdAMA1 available due to the extremely high parasitemia obtained in vitro and showed conclusively that the processed fragments of BdAMA1 (48, 44, and 37 kDa) (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…[17][18][19]23,24 Loop 1 of domain III binds to the erythrocyte membrane protein Kx, and invasion of Kx null erythrocytes is reduced, indicating a significant role of AMA-1 and Kx in parasite invasion of erythrocytes. 25 We have previously shown the development of synthetic peptides based on these two proteins for inclusion into a multivalent subunit malaria vaccine. [26][27][28][29][30] Peptide UK-39 is based on the NANP repeats of CSP 30 and peptide AMA49-C1 on the erythrocyte-binding loop 1 of domain III from AMA-1.…”
Section: Introductionmentioning
confidence: 99%